Assessment of indoor volatile organic compounds in Head Start child care facilities. (15th October 2019) - Vu, Danh C.; Ho, Thi L.; Vo, Phuc H.; Bayati, Mohamed; Davis, Alexandra N.; Gulseven, Zehra; Carlo, Gustavo; Palermo, Francisco; McElroy, Jane A.; Nagel, Susan C.; Lin, Chung-Ho
Abstract: Exposure to volatile organic compounds (VOCs) in child care environments has raised a public concern. This study aimed to characterize indoor VOCs in four facilities of Head Start programs in Kansas city, Missouri, investigate seasonal and spatial variations in VOC levels, and assess health risks associated with children's VOC exposure. In total, 49 VOCs including aromatic and aliphatic hydrocarbons, aldehydes, glycol ethers, esters and chlorinated hydrocarbons were identified and quantified in the facilities. Significant differences were noted for the VOC concentrations among the facilities. Toluene was the most abundant aromatic hydrocarbon detected in all the air samples, with a narrow median concentration range of 2.17–3.07 μg/m 3 . 2-(2-Methoxyethoxy)ethanol never reported in prior research was detected in only one facility in this study, with the median (range) concentration of 0.83 (<LOD, 5.64) μg/m 3 . The VOC concentrations in ground-floor classrooms differed significantly from those in basement classrooms. The VOC profiles varied substantially between fall and winter. Identified emission sources of VOCs included vehicle-related emission, solvent-related emission, building materials, personal care products and household products. Through health risk assessment, potential carcinogenic compounds (i.e., benzene, ethylbenzene, naphthalene, 1, 4-dichlorobenzene, tetrachloroethylene and trichloroethylene) were of concern as the total cancer risk exceeded 10 −6 . Future research on children's chronic exposure to these pollutants needs to further assess their possible additive and/or synergistic effects on children's health and development. Highlights: Forty-nine VOCs were identified and quantified in the studied Head Start facilities. Spatial and seasonal variations in levels of VOCs were determined. Emission sources of VOCs were identified using principal component analysis. Children's exposure to potentially deleterious VOCs occurred in these facilities.